Highway design and traffic safety engineering handbook - Lamm, Ruediger (McGraw-Hill handbooks, 1999)
This is the first book to present a thoroughly scientific and practical approach to designing highways for maximum safety. Based on original research plus scrupulously collected data amassed over more two decades in different continents by the main author, this important book originates vital criteria for safe design and shows you how best to achieve roads with the lowest possible accident risk and severity rates. In addition, this valuable and necessary resource gives you serious help coordinating safety concerns with important economic, environmental, and aesthetic considerations. Overall the book is an invaluable source of information for educators, students, scientists, highway agencies, and consultants in the field of highway design and traffic safety engineering.